A matter of consciousness – Introducing Zora Neale Hurston and Katie G. Cannon - Hans S.A. Engdahl (AOSIS, 2021)
This article involves a close reading of two African American authors, Zora Neale Hurston, an acclaimed novelist and Katie Cannon, an influential theological ethicist. Texts from Steve Biko on black consciousness and from James Cone on liberation theology are used as methodological tools in trying to ascertain the degree to which Hurston and Cannon espouse a black (womanist) consciousness. A strong resonance of black consciousness will indeed be found in Hurston’s and Cannon’s texts. The conclusion drawn is that not only is there a resonance of black consciousness, but both writers also give proof of a black womanist consciousness that reveals new knowledge. Cannon’s oeuvre also begs the question of epistemological privilege. In addition, an animated critique is registered between these women scholars and male colleagues, in the world of fiction (Richard Wright) and academia (white European males).